Effects of Oil Consumption, Urbanization, Economic Growth on Greenhouse Gas Emissions: India via Quantile Approach - Khan, Uzma (International Journal of Energy Economics and Policy, 2023)
Although low-carbon economic growth has been emphasized in both the Paris Agreement and the Sustainable Development Goals, this is the first study to examine the interplay between oil consumption, urbanization, and economic growth in India’s GHG emissions from 1965 to 2021. A quantile regression analysis found that a one percent rise in greenhouse gas emissions is linked to a 0.34 percent rise in economic growth, a 0.599 percent rise in oil consumption, and a 0.28 percent drop in urbanization. Using the Granger causality technique, researchers found that CO2 emissions cause economic development and urbanization in only one direction. On the other hand, oil consumption only has a one-way influence on carbon emissions and urbanization, and economic expansion only has a one-way effect on urbanization.